The Growing Phenomenon Of Slum Areas And Their Impact On The Development Sectors Before The Events Of 10/6/2014. Analytical Study in Mosul city - H. Alsabaawi, Yousif; H. Ayoub, Harith (Opción, 2019)
The human always seeks for managing his environment for his benefit, al- though the environment factors may not help him or even may impede this matter, and this what happen in Iraqi cities, Mosul city which was the first one of those (which has a great historical dimension) due to the effect of wars & violence which are lead people not get their needs. Although Mosul citizen wishes to see various development sectors are working (even in the minimum level), But the urgent demand for residence make his forget these measures and to live in the surrounding of city, even in random areas (not systematic), and he is find an alternatives for hem through the participation of people re- siding near by in nonrandom areas (systematic) in the development sectors (which are also in bad quality since years) this situation led to a lot of negative feedback effects on development sectors of these area (systematic) as well as on the social and ecology of the random areas (not systematic) it selves.